1987
DOI: 10.1212/wnl.37.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Antineural antibodies in the serum of patients with amyotrophic lateral sclerosis

Abstract: Sera from 12 patients with amyotrophic lateral sclerosis (ALS) and 18 controls were screened for antineural antibodies using immunoblotting. No consistent differences were detected between ALS patients and controls, although antibodies to 52,000- and 70,000-dalton proteins in mouse spinal cord were somewhat more common in ALS sera. Antibodies to a protein of approximately 150,000 to 200,000 daltons were also evident. The 70,000- and 52,000-dalton proteins were detected in brain, cerebellum, and liver as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Out study demonstrated the presence of antibodies to spinal-cord proteins in sera from patients with MND and other neurological diseases, as has been reported by Brown et al [1] and Klett et al [2], Among these, ALS-1 reacted with 65-and 66-kD insoluble proteins in the crude nuclear subfraction although it has not been deter mined whether these proteins are components of the nuclear membrane. ALS-1 had the highest titer of all.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Out study demonstrated the presence of antibodies to spinal-cord proteins in sera from patients with MND and other neurological diseases, as has been reported by Brown et al [1] and Klett et al [2], Among these, ALS-1 reacted with 65-and 66-kD insoluble proteins in the crude nuclear subfraction although it has not been deter mined whether these proteins are components of the nuclear membrane. ALS-1 had the highest titer of all.…”
Section: Discussionsupporting
confidence: 56%
“…Brown et al [1] reported that antineural antibodies which reacted with 52, 70-and 150-to 200-kD proteins in mouse spinal cord were detected in ALS and some controls by the immunoblotting technique using sera diluted from 1:20 to 1:100. They demonstrated that some sera reacted with the neurofilaments and nuclear membrane of all cells immunohistochemically using the avidin-biotin technique with sections freshly prepared from mouse spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series of patients with pure ALS we observed no anti-nervous system staining using standard methods. Moreover, anti-nervous system antibodies have been described in ALS patients both with and without tumor [1,4,7,12,15,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the observation of a sproutinhibiting effect of some of the patients' sera, if confirmed, would suggest that the motor nerve terminal itself may be an important site in the pathogenesis of ALS (see later). Finally, there are several reports of immunoglobulins from ALS patients binding to spinal cord cells or extracts [19, 203, but some of these findings have not been replicated [21,22). As [24) found an increased incidence of the HLA A3 histocompatibility type in patients with "classical" rapidly progressive ALS and an increased incidence of HLA B12 in those with slowly progressive forms, but others have failed to replicate these observations [25).…”
mentioning
confidence: 99%